(3QSGdI SGMbjdi RGOg aj BOGH GdHMK hGdefGXQIs - (3SGLbdj RGOg , SGLbdj RGOg,J (B1150 (3g` s
(3ChdgG (B:s
(3jbhd GdHGFS GdabjQ eMeO GdeQYTi GdeOYh HSGMbdi RGOg CcQeg Gddg SHMGfg HGdahR hGdSYGOI gPG JbQjQ GdbhGfjf GdeJOGhdI ef Yde GdefGXQI cJHJg JNdUkG Yf EbJQGM HYV GdWdHI s
(3BNQgG (B:s
(3hEf de JTJed Ydi TF efgG aGYde Gf GdbjGS eQcH cbhdfG ai EKHGJ Cf GdYGde dg eDKQ dCf cd eJZjQ MGOK hGdeWhjGJ JMJGL Edi HSW hdjcf BNQ GdcdGe GdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B14s
Keywords: (3GdadSaI hGdefWbs